Greater Breast Support Alters Trunk and Knee Joint Biomechanics Commonly Associated With Anterior Cruciate Ligament Injury - Fong, Hailey B.; Nelson, Alexis K.; Storey, Julie E.; Hinton, Jay; Puppa, Melissa; McGhee, Deirdre; Greenwood, Daniel; Powell, Douglas W. (Frontiers in Sports and Active Living, 2022)
Objective The female breast is a passive tissue with little intrinsic support. Therefore, women rely on external breast support (sports bras) to control breast motion during athletic tasks. Research has demonstrated that lower levels of breast support are associated with altered trunk and pelvis movement patterns during running, a common athletic task. However, no previous study has identified the effect of sports bra support on movement patterns during other athletic tasks including landing. Therefore, the purpose of this study was to examine the effects of breast support on trunk and knee joint biomechanics in female collegiate athletes during a double-leg landing task. Methods Fourteen female collegiate athletes completed five double-leg landing trials in each of three different sports bra conditions: no support, low support, and high support. A 10-camera motion capture system (250 Hz, Qualisys, Goteburg, Sweden) and two force platforms (1,250 Hz, AMTI, Watertown, MA, USA) were used to collect three-dimensional kinematics and ground reaction forces simultaneously. Visual 3D was used to calculate trunk segment and knee joint angles and moments. Custom software (MATLAB 2021a) was used to determine discrete values of dependent variables including vertical breast displacement, knee joint and trunk segment angles at initial contact and 100 ms post-initial contact, and peak knee joint moments. A repeated measures analysis of covariance with post-hoc paired samples t-tests were used to evaluate the effect of breast support on landing biomechanics. Results Increasing levels of breast support were associated with reductions in peak knee flexion (Right: p = 0.008; Left: p = 0.029) and peak knee valgus angles (Right: p = 0.011; Left: p = 0.003) as well as reductions in peak knee valgus moments (Right: p = 0.033; Left: p = 0.013). There were no changes in peak knee extension moments (Right: p = 0.216; Left: p = 0.261). Increasing levels of breast support were associated with greater trunk flexion angles at initial contact (p = 0.024) and greater peak trunk flexion angles (p = 0.002). Conclusions Lower levels of breast support are associated with knee joint and trunk biomechanical profiles suggested to increase ACL injury risk.